New Zealand government and politics - Miller, Raymond 1953- (Oxford University Press, 2003)
"New Zealand Government and Politics is the leading undergraduate textbook for students of New Zealand political science. This third edition, featuring seven new chapters, includes a review of the major political events of the period 1990-2003, including analyses of the 2002 election campaign and results, the formation of the new Labour-led government, the parliamentary review of proportional representation, and recent changes to the party system."--Jacket.